Пластичности артериального русла сердца и легких собак в условиях нарушенного кровообращения - Мельман, Е.П.; Максимук, Ю.А.; Шевчук, М.Г. (Вестник зоологии, 1969)
In experimental myocardial infarction, induced in dogs by elimination of the branches of the left coronary artery, in the early experiments the anatomic insufficiency of intercoronal anastomoses and collaterals is observed, owing to which they did not ensure the fast restoration of blood circulation in heart in previous volume. In course of time the reactive reconstruction of intracoronary anastomoses takes place, providing more and more blood influx to the ischemized area of myocardium. After elimination of the branches of pulmonary artery the anatomic insufficiency of interarterial anastomoses appears also in the lungs. It is more pronounced in comparison with the heart.